INVENTORY AND SITUATIONAL ANALYSIS OF RECREATIONAL AND WATER PROTECTION INFRASTRUCTURES ON WATER BODIES OF THE SOUTH OF WESTERN SIBERIA - Irina V. Andreyeva; Svetlana V. Tsilikina (Водное хозяйство России: проблемы, технологии, управление)
The article presents results of the inventory of recreation facilities in the river basins (the Aley, the Charysh, and the Chumysh) and lakes (Bolshoye Yarovoe, Zavyalovo, and Chany) in the South of Western Siberia. The article shows the actual interaction of elements of recreational and water protection infrastructure on recreation-significant areas of the coast. Out of 72 objects identified in the study area, 19 are located within the water protection zone of water bodies. Potential conflicts of land use and benefits of joint development of recreational and water protection facilities were assessed on the coasts. For spatial analysis, specialized indicators are proposed: the coastal protection index and the recreational reserve index. The results of calculation of indices on the example of basins of key water bodies are presented and their differentiation by the degree of protection of the coast and the level of development of recreational infrastructure is shown. Conclusions are drawn about the need to clarify the theoretical and methodological tools for making tactical and strategic decisions in the management of recreational areas.